Phytoremediation: A plant-based remediation technology to clean up the contaminants - Meena, Vasudev; Dotaniya, M L; Meena, B P; Das, H (Indian Farming, 2019)
Environmental pollution has become a serious public health concern because it is a major source of health risk that causes several serious diseases worldwide. Heavy metal contamination is one of the most important hazardous pollutants which can even lead to death after long time exposure. Due to urbanization and industrial developments, the environmental pollution by heavy metals has increased. Trace metals, called potentially toxic trace elements, cause degradation of the active surface of the earth and constitute a major threat to the food chain of plants, animals and humans. Phytoremediation is a good remediation technology to clean up contaminants from the environment by using green plants.